Can we eradicate trachoma? A survey of stakeholders. Issue 8 (27th August 2020) - Oldenburg, Catherine E; Aragie, Solomon; Amza, Abdou; Solomon, Anthony W; Brogdon, Jessica; Arnold, Benjamin F; Keenan, Jeremy D; Lietman, Thomas M
Abstract : Background/Aims: Although tremendous progress towards the 2020 goal of global elimination of trachoma as a public health problem has been made, it will not be achieved. Future targets are now being considered. One option is changing the goal to eradication . We surveyed trachoma experts to assess beliefs related to trachoma eradication and determine perceived obstacles to achieving it. Methods: We conducted a survey at the beginning of a trachoma eradication session at the 2019 Coalition for Operational Research on Neglected Tropical Diseases meeting in National Harbor, Maryland, USA. We asked respondents what the most important goal of azithromycin mass drug administration was for trachoma (control, elimination of infection or eradication) and if and when they believed trachoma eradication would occur. We then asked what the biggest obstacles were to global eradication. Results: Fifty-six surveys were returned (95%). Most (91%) participants reported that the most important goal of azithromycin mass drug administration was control or elimination of infection, and 24% of participants reported that global eradication was not possible. Of the 76% who reported a year by which they believed trachoma could be eradicated, most fell between 2040 and 2050. Commonly cited barriers to global eradication included lack of surveillance tools to confirm eradication or monitor for infection recrudescence (32%) and lack of resources (23%). Conclusions: Development of alternative indicators for trachoma surveillance and continued investment in trachoma programmes, particularly focused support in the most heavily affected populations, might increase enthusiasm for the feasibility of eradication.